Implementasi SIJAPRI Berbasis Website sebagai Solusi Integrasi dan Pengelolaan Data Ketenagakerjaan - Firiminus Kili Doze; I Made Dwi Ardiada; Prastyadi Wibawa Rahayu (TIN: Terapan Informatika Nusantara, 2026)
The Department of Industry and Manpower of Badung Regency still faces challenges in managing job seeker, company, and job vacancy data that are not yet integrated. Manual administrative processes reduce service efficiency and delay the preparation of employment reports. This study aims to develop the Badung Productive and Independent Job Ready Information System (SIJAPRI), a web-based information system designed to integrate employment services while evaluating its functionality and usability. The system was developed using the Waterfall method, which consists of the requirements analysis, system design, implementation, testing, and maintenance phases. System functionality was evaluated using Black Box Testing, while usability was assessed using the USE Questionnaire. The results indicate that SIJAPRI successfully integrates the management of job seeker data, company data, job vacancies, job applications, recruitment selection processes, and employment reporting. All system functions operated according to the specified requirements based on the Black Box Testing results. The usability evaluation using the USE Questionnaire achieved a score of 87.36%, which falls into the very good category. This research contributes by developing a website-based information system known as SIJAPRI (Badung Siap Kerja Produktif dan Mandiri), which integrates job seeker services, companies, recruitment processes, and employment reporting into a single platform; it also provides a functional evaluation using Black Box Testing and a usability assessment using the USE Questionnaire to serve as a foundation for developing digital-based employment services within government agencies.